Are Veterinary Costs and Socioeconomic Status Risk Factors for Companion Animal Relinquishment in the Republic of Korea? - HyungChul Rah; Seok-Hwa Choi (Animals, 2023)
More than 110,000 companion animals are sent to shelters each year due to abandonment in Republic of Korea, and there is a need to analyze the causes of the relinquishment of animals and implement appropriate policies. Veterinary costs have been blamed for this issue in Republic of Korea above the reported leading causes of socioeconomic status of owners, cost and behavior issues of the animals, or housing restrictions. However, it is rare to find supporting evidence. In this study, we aimed to determine whether veterinary costs and socioeconomic factors are related to animal relinquishment in Republic of Korea. Multiple regression models were used to test if veterinary costs and socioeconomic indicators can account for relinquishment in 128 regions of Republic of Korea in 2020 and 2021. When five independent variables (two veterinary cost data and three socioeconomic indicators) were included, the regression model showed significance in explaining pet relinquishment in 2020, with an adjusted coefficient of determination of 0.3956. Pet relinquishment can also be explained by the same five variables for 2021, with an adjusted coefficient of determination of 0.391 with p < 0.0001. The findings suggest that intervention to reduce companion animal relinquishment in Republic of Korea should focus on lightening the financial burdens of owners as the socioeconomic status of a community worsens.